Impacts of climate changes on spatio-temporal diversity patterns of Atlantic Forest primates - Adriana Almeida de Lima; Milton Cezar Ribeiro; Carlos Eduardo de Viveiros Grelle; Míriam Plaza Pinto (Perspectives in Ecology and Conservation, 2019)
Changes in Earth's climatic conditions may affect the geographic distributions of species causing variations in diversity patterns through space and time. Projections of species distributions over time can measure how future climate scenarios will affect communities. We investigated how climate changes scenarios will influence primate biodiversity patterns in the Atlantic Forest. Specifically: (i) where are the largest changes in species richness expected? (ii) the spatial pattern of beta diversity will undergo homogenisation or heterogenisation? and (iii) where will occur the major changes in temporal beta diversity? We generated current and future species distribution models for Brazilian Atlantic Forest primates. We analysed the changes in the spatio-temporal patterns of alpha and beta diversity. Current high richness patterns will be maintained in future scenarios, with richer areas concentrated in the coastal zones. Regions closer to Cerrado will face a reduction in primate richness. Changes in richness will occur predominantly due to species loss. Communities will be more spatially heterogeneous in the future, with increased beta diversity. The heterogenisation may be driven by the reduction of species geographic distributions. The highest temporal changes will occur mainly in the midwest and the central region of the biome. Climate changes will cause primates diversity changes in both space and time. These changes will not be homogeneous through the Atlantic Forest. Our study is informative at a large spatial scale, providing an outlook on the impact of climate change on primate diversity, and indicating places of primates’ biodiversity maintenance, loss or gain due to climate change.